The Relationship between Social Support and Subjective Well-Being: A Meta-Analysis - Hikmah, Nur; Erlangga, Erwin; Sugiarti, Lucia Rini (Journal Social Civilecial, 2026)
Subjective well-being has become an important indicator of individual quality of life and psychological functioning, while social support is frequently regarded as a key factor influencing well-being outcomes. However, empirical findings regarding the relationship between social support and subjective well-being remain inconsistent across studies and contexts. Therefore, this study aimed to examine the overall relationship between social support and subjective well-being through a meta-analytic approach. This study employed a quantitative meta-analysis by synthesizing empirical studies published between 2020 and 2026. The literature search was conducted systematically through the Scopus database using several related keywords associated with social support and subjective well-being. After applying inclusion and exclusion criteria, six empirical studies with a cumulative sample of 3,087 participants were included in the analysis. Statistical analysis was performed using a random-effects model with Fisher’s Z transformation to estimate the pooled effect size and heterogeneity across studies. The findings revealed that social support demonstrated a positive but weak and statistically non-significant relationship with subjective well-being (pooled effect = 0.137; p 0.005). In addition, substantial heterogeneity was identified, indicating that the relationship varied considerably across populations, contexts, and measurement approaches. The results suggest that social support does not function as a universally consistent predictor of subjective well-being, but rather operates as a context-dependent relational resource influenced by cultural, psychological, and organizational conditions. This study contributes to management and psychological literature by emphasizing the complexity of social support and encouraging more context-sensitive approaches in future well-being research.